2010
DOI: 10.4049/jimmunol.1000119
|View full text |Cite
|
Sign up to set email alerts
|

A Proinflammatory Role for Proteolytically Cleaved Annexin A1 in Neutrophil Transendothelial Migration

Abstract: Neutrophil extravasation, a critical component of innate immunity must be tightly regulated to prevent inadvertent or prolonged inflammation and subsequent tissue damage. We have shown previously that endothelial ERK1/2 signaling essential for neutrophil transendothelial migration is induced by a soluble factor produced by activated neutrophils. In this study, we demonstrate that the soluble neutrophil factor is a truncated form of annexin A1 (AnxA1) that can be generated by calpain 1 cleavage of the N terminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…Thus, modulation of endogenous AnxA1 pool might be an important mechanism to resolve inflammatory responses. This can be even of more acute importance because the 33-kDa form of AnxA1 displays proinflammatory effects by promoting ERK1/2 activation and neutrophil transendothelial migration (16). To our knowledge, the first concept that the 33-kDa AnxA1 form might have proinflammatory properties has been suggested by findings in fluid samples from cystic fibrosis patients (15).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, modulation of endogenous AnxA1 pool might be an important mechanism to resolve inflammatory responses. This can be even of more acute importance because the 33-kDa form of AnxA1 displays proinflammatory effects by promoting ERK1/2 activation and neutrophil transendothelial migration (16). To our knowledge, the first concept that the 33-kDa AnxA1 form might have proinflammatory properties has been suggested by findings in fluid samples from cystic fibrosis patients (15).…”
Section: Discussionmentioning
confidence: 81%
“…However, within this microenvironment AnxA1 is vulnerable to be cleaved at the N-terminal region by proteases including NE and PR3, generating the 33-kDa isoform of poorly known properties (13,14). Studies have shown that the 33-kDa isoform of AnxA1 may be associated with proinflammatory effects (15,16). Congruently, cleavage-resistant (CR) AnxA1 exhibited greater anti-inflammatory effect compared with the parent protein, in different animal models of inflammation (17,18).…”
mentioning
confidence: 99%
“…ANXA1 cleavage promotes neutrophil transendothelial migration (17) and regulates EGF-triggered signaling and AA production in normal and malignant squamous epithelial cells (14). Recently, an ANXA1 mutant (A11R/V22K/V36K) was reported to be resistant to cleavage by all proteases present in PMN cell extracts (18).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal peptide is known to be cleaved by a number of proteases, including elastase, calpain, plasmin, cathepsin D, and proteinase 3 (11)(12)(13)(14), and is also phosphorylated to regulate the activity of the protein (15,16). N-terminal truncated ANXA1 has a proinflammatory effect and promotes neutrophil transendothelial migration (17). Truncated ANXA1 has also been linked to an epidermal growth factor (EGF)-triggered signaling pathway involving cytosolic phospholipase A 2 (cPLA 2 ) in normal and malignant squamous epithelial cells (14).…”
mentioning
confidence: 99%
“…ANXA1 has been identified in various cell types, where it is thought to be important in biological functions. Originally described as having an anti-inflammatory effect similar to that of glucocorticoids, ANXA1 has been demonstrated to be involved in various cellular processes, including inflammation [1], leukocyte migration [2], cell growth [3], and differentiation [4]. As ANXA1 does not have signal peptide sequences, it is thought to be secreted unconventionally [5].…”
Section: Introductionmentioning
confidence: 98%